Dakwah Berbasis Pemberdayaan Ekonomi Pada Program Misykat DT Peduli Di Kelurahan Rahma Kota Lubuklinggau - Sauti, Sapardi; Solimin, Solimin; Hanif, Nur Muhammad Usman (STAI Bumi Silampari, 2024)
During the era of globalisation, we will be presented with the disharmony of the crisis of human values with the tension of Islamic norms along with the advancement of science and technology (IPTEK). Therefore, the correlation between aspects of religion / da'wah, social communication, and science needs to be integrated in the delivery of Islamic religious education and social character building. The main focus is how da'wah and Islamic religious education can build social character in accordance with Islamic values in the midst of rapid social change. The study presented in this research uses a literature review to collect, evaluate and synthesise information from various sources, thus building a comprehensive understanding of the topic discussed. This research found that da'wah and Islamic religious education are very important in building social character in accordance with Islamic values. The concept of effective da'wah communication can help in transforming the values of Islamic religious education into relevant da'wah applications in the modern era. Islamic religious education aims to improve the quality of human resources and create a decent situation for life and the environment. Da'wah and Islamic religious education have an important role in building social character in accordance with Islamic values. In the modern era, da'wah must be able to adapt to the development of science and technology and globalisation to remain relevant and effective. This research emphasises the importance of integration between da'wah and communication to achieve sustainable da'wah goals.